PERTANGGUNGJAWABAN PIDANA TERHADAP ANAK SEBAGAI PELAKU TINDAK PIDANA PENCURIAN DENGAN KEKERASAN (Studi Putusan Perkara Nomor: 4/Pid.Sus-Anak/2017/PN Pbr) - Dyane '; Mexsasai Indra; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Provision of criminal sanctions against children as perpetrators of criminal acts of theft with violence and denial which have complied with the provisions of Article 365 paragraph (2) to the 2nd Criminal Code (Penal Code) with imprisonment for 1 (one) year and 6 (six ) month for perpetrators who are aged 14 years is considered not appropriate when viewed from the concept of punishment of children. A special imprisonment has a negative impact on the child's development. Sanctionsweet against misbehaved children (juvenile delinquency) may be given action in the provision of Article 82 paragraph (1) of Law Number 11 Year 2012 on Child Criminal Justice System. type of normative juridical research, whose purpose with normative juridical research is a study that discusses legal principles, legal system, law-law level, legal history, and comparative law. Judging from the nature of the research used Descriptive, The purpose of this study is to provide a systematic description of the level of self-law in the criminal responsibility of children as perpetrators of theft with violence. Sources of data used, primary data and secondary data and tertiary data, data data techniques in this study with literature review. From the results of this study the authors can be concluded. First, the responsibility of the child in committing a crime is a responsible and ready child to be investigated, prosecuted and tried in court. It's just that there are provisions where a child is not the same as the parents. Secondly, the judge in making a legitimate child criminal verdict is sufficient only to base on what has been written and regulated in the Act. And in juridical considerations in the case of children, there is clearly a difference regarding the provisions of material offenses and the provisions of the formal offense. Keywords: Judge's Verdict - Criminal - Child Account